Pelvic Floor Distress Inventory (PFDI)-20 Score In Patients With Pelvic Organ Prolaps (POP) - Yulia Margaretta Sari; Mila Permata Sari (Universitas Andalas, 2024)
Background :Pelvic organ prolapse (POP) is a common and benign condition in women. It was the fall of one or more components of the vagina and uterus, which allows surrounding organs to herniate into the vaginal area, a disease known as cystocele, rectocele, or enterocele. The PFDI-20 score has been used to evaluate symptoms and quality of life in all POP patients. Objectives : To analyze the PFDI-20 score in patients with POP. Method : An observational study involving POP patients was undertaken at RSUP Dr. M. Djamil Padang from December 2023 to January 2024. The variables include demographic information (age, parity, obstetric and gynecological history) gathered from medical records, as well as complaints and POP symptoms obtained through an interview using the Indonesian PFDI-20 score. Data was analyzed univariately and bivariately. Statistical significance was set at p<0.05, and statistical analyzes were conducted using Kruskal-Wallis. The statistical program used for the analysis was SPSS 25.0. Results : Twenty-eight ladies participated. Their average age was 64.43 years (SD=10.49), parity number was 4.5 (SD=2.2), and PDFI-20 score was 136.61 (SD=54.21). In terms of POP, 53.6% (15) were IV. In terms of prolapse type, all patients had uterine prolapses, with the majority also having cystocele and rectocele (96.4%). Total vaginal hysterectomy (TVH) was performed in 82.1% (23), with over half of the patients undergoing anterior colporrhaphy (AC), posterior colpoperineorrhaphy, or colpocleisis. The majority of the complaints concerned inactive sexual activity (92.0%) and frequency (64.3%). The bivariate analysis with Kruskal Wallis test revealed no statistically significant relationships between PDFI-20 score and degree of POP (p<0.05). Conclusion : Although we were unable to identify a significant correlation, the PFDI-20 score was demonstrated to be a reliable tool for assessing symptoms and quality of life in all POP patients.